Analysis of methods for supplier selection - Mendes, Luís (2014)
This work seeks to determine the criteria and methods used in the problem of selecting suppliers, thus contributing to the support of entities wishing to start a selection of suppliers more effectively. To achieve these objectives, an analysis was performed of articles that make the literature review of the methods and criteria from the year 1985 to the year 2012. With the data obtained from these reviews, it was possible to verify which are the three main methods used over the years, namely data envelopment analysis (DEA), Analytical hierarchy process (AHP) and Fuzzy set theory and the main criteria used in the selection of suppliers. In this work, we present an overview of the decision making and the methods used in multi-criteria decision making. It’s tackled the problem of supplier selection, the process of selection and the reviews of literary methods and criteria used in recent years. Finally is presented the contribution to the selection of suppliers of the study conducted during the development of this dissertation, being presented and explained the main methods of selection of suppliers as well as the criteria used.